Cytogenetic And Cytotoxic Indicators Of Buccal Epithelium In Patients With Chronic Recurrent Aphthous Stomatitis - Alimova D.M., Bekjanova O.E., Daminova N.R., Astanakulova M.M., Alimova S.Kh. (International Journal of Advanced Science and Technology, 2020)
In the Republic of Uzbekistan, the frequency of chronic recurrent aphthous stomatitis among all diseases of MOP is 6.22% and tends to increase, therefore, the study of the cytogenetic and cytotoxic parameters of buccal epithelium in patients is of undoubted practical interest [5].